Studies on Energy, CO2s and Water on the African Continent - (:unkn) unknown (My University, 2021)
African nations share a common situation in that they pollute little in terms of CO2s globally speaking, but at the same time global warming will likely have terrible consequences for the continent, set to face a sharp population increase. African governments have promised to contribute towards the COP21 objectives of decarbonisation by transforming their energy systems. They have now access to few energy resources, which is conducive to their poverty. New renewables belong to the future (solar, wind, geo-thermal), whereas old renewables -wood, coal-– are a thing of the past. The coal or oil and gas dependent giants must start energy transformation, as must the many countries relying upon traditional biomass, or charcoal. The use of wood coal is simply too large for the survival of the African forests. Africa need lots of energy to handle the coming crisis of potable water, as lakes and rivers are shrinking and degraded by pollution, dams and overfishing.
Keywords: African Research